PENGEMBANGAN MEDIA INTERAKTIF BERBASIS MIND MAPPING UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MATERI STRUKTUR PASAR - Meilani Puji Lestari; Muhammad Abdul Ghofur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students often experience difficulties in understanding Market Structure because the topic is abstract, complex, and requires the ability to distinguish the characteristics of different market types. Furthermore, the instructional media currently used have not been able to clearly visualize the relationships among concepts, highlighting the need for more visual and interactive learning media. The novelty of this study lies in the integration of Google Sites, Quizizz, and mind mapping into a single interactive learning medium specifically designed to enhance students' conceptual understanding of Market Structure. This study aimed to develop an interactive mind mapping–based learning medium for the Market Structure topic for tenth-grade senior high school students and to examine the improvement in students' conceptual understanding after using the developed medium. This research employed a Research and Development (R&D) approach using the ADDIE model, limited to the development stage. A limited field trial was conducted with 32 tenth-grade students at SMA Negeri Bareng. The feasibility of the learning medium was evaluated by media, subject matter, and language experts, while improvements in students' conceptual understanding were analyzed using the Wilcoxon Signed-Rank Test and the Normalized Gain (N-Gain) test. The results indicated that the developed medium achieved feasibility scores of 83.33% from the media expert, 82.66% from the subject matter expert, and 81.25% from the language expert, all of which were categorized as highly feasible. The Wilcoxon Signed-Rank Test revealed an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), while the average N-Gain score was 0.4464, indicating a moderate level of improvement. These findings demonstrate that the interactive mind mapping–based learning medium is highly feasible for instructional use and effectively improves students' conceptual understanding of Market Structure.